Efficient two-step chemoenzymatic conjugation of antibody fragments with reporter compounds by a specific thiol-PEG-amine Linker, HS-PEG-NH2 - Haruya Sato; Yukiko Kataoka; Youichi Nishikawa; Daiki Okano; Mami Nagai; Yoshio Yamauchi; Masato Taoka; Katsuki Naitoh (PLoS ONE, 2025)
Chemoenzymatic conjugation of antibodies with reporter compounds offers broad applicability for detecting target antigens in the context of in vitro research and diagnostics. For conjugation, a bifunctional linker with a protected thiol and an amino group, serving as a transglutaminase substrate, is often employed. However, protective groups require an additional deprotection step during synthesis. To overcome this limitation, we selected a long-chain thiol-PEG-amine (HS-PEG) linker as the substrate. The HS-PEG linker exhibited minimal S–S bond dimerization in solution and was efficiently conjugated to Fab containing the transglutaminase-specific sequence tag (Q-tag), retaining the free state of the SH group. Using this SH group, a reporter compound containing two types of activated maleimides, Alexa488 or the red algae-derived fluorescent dye phycoerythrin, was conjugated to Fab. Both conjugates formed uniform structures in just two synthetic steps without compromising antigen-binding activity. Among the conjugates, phycoerythrin conjugated with multiple Fab molecules showed higher activity than that conjugated with fewer molecules in fluorescence enzyme-linked immunosorbent assays (ELISA) and flow cytometry. These results indicate that the chemoenzymatic approach using the HS-PEG linker and transglutaminase facilitates uniform Fab conjugation with reporter molecules for in vitro research and diagnostic applications. This method can expand the application of chemoenzymatic modification of antibody fragments by simplifying the conjugation process and reducing the formation of by-products.